Revising the Taxonomic Distribution, Origin and Evolution of Ribosome Inactivating Protein Genes - Lapadula, Walter Jesús (2013)
Ribosome inactivating proteins are enzymes that depurinate a specific adenine residue in the alpha-sarcin-ricin loop of the large ribosomal RNA, being ricin and Shiga toxins the most renowned examples. They are widely distributed in plants and their presence has also been confirmed in a few bacterial species. According to this taxonomic distribution, the current model about the origin and evolution of RIP genes postulates that an ancestral RIP domain was originated in flowering plants, and later acquired by some bacteria via horizontal gene transfer. Here, we unequivocally detected the presence of RIP genes in fungi and metazoa. These findings, along with sequence and phylogenetic analyses, led us to propose an alternative, more parsimonious, hypothesis about the origin and evolutionary history of the RIP domain, where several paralogous RIP genes were already present before the three domains of life evolved. This model is in agreement with the current idea of the Last Universal Common Ancestor (LUCA) as a complex, genetically redundant organism. Differential loss of paralogous genes in descendants of LUCA, rather than multiple horizontal gene transfer events, could account for the complex pattern of RIP genes across extant species, as it has been observed for other genes.